Atlas of Conducted Electrical Weapon Wounds and Forensic Analysis - Ho, Jeffrey D.; Ho, Jeffrey D.; Dawes, Donald M.; Dawes, Donald M.; Kroll, Mark W.; Kroll, Mark W. (Springer New York : Imprint: Springer, 2012)
Atlas of Conducted Electrical Weapon Wounds and Forensic Analysis provides a comprehensive publication on the subject of Conducted Electrical Weapon (CEW) wounds and signature markings created by this class of weapon. This volume will serve as a very useful resource for all professions tasked with assisting persons that have allegedly been subjected to a CEW exposure. The volume provides an introduction to basic CEW technology and the types of CEWs currently available. It also serves as a comprehensive pictorial atlas of signature markings that CEW exposures make in the immediate and more remote post-exposure periods. Also, it discusses the ability of forensic specialty examinations of the CEW itself to aid in the determination of whether the alleged CEW exposure is consistent with the objective evidence and the subjective statements. Finally, this text addresses the important and growing area of factitious CEW markings that will be useful for consideration by investigators and litigators. Atlas of Conducted Electrical Weapon Wounds and Forensic Analysis provides an objective atlas of evidence for reference that will benefit those professionals who often must make diagnostic, treatment or legal judgments on these cases including Emergency and Primary-Care Physicians, Medical Examiners, Forensic Pathologists, Coroners, Law Enforcement Investigators, and Attorneys.